Simulation of mechanical characteristics of tennis racket string bed considering string pattern - Matsuda, A.; Nakui, M.; Hashiguchi, T. (Proceedings, 2018)
The effect of string pattern on the mechanical characteristics of a tennis racket were simulated numerically. A numerical simulation program to evaluate deformation of the string bed of a tennis racket was developed using the finite element method. The formulation of a numerical simulation code is described in this paper. The applicability of the developed simulation program was investigated by comparing experimental results of loading tests on string bed specimens, for which the distance between strings was 12 mm. The out-of-plane stiffness and sliding characteristics of strings of an actual racket were simulated using the developed simulation code.